Precision and Bias of Target‐Controlled Prolonged Propofol Infusion for General Anesthesia and Sedation in Neurosurgical Patients. (9th January 2018) - Cortegiani, Andrea; Pavan, Alessandra; Azzeri, Fabio; Accurso, Giuseppe; Vitale, Filippo; Gregoretti, Cesare
Abstract: The aim of this study was to determine the relationship, precision, and bias of a propofol target‐controlled infusion (TCI) system during prolonged infusion in neurosurgical patients. We retrospectively included patients undergoing general anesthesia for elective neurosurgical removal of brain tumors and postoperative sedation in the intensive care unit over a period of 3 months. TCI of propofol (Diprifusor – Marsh model) and remifentanil were used for general anesthesia and sedation. We compared propofol blood concentration (Cmeas ) measured by liquid chromatography–mass spectroscopy with predicted concentrations (Cpred ) by the TCI system at 40 minutes (T0), 2 hours (T1), and 4 hours (T2) and every 8 hours after starting the drug infusion and at the time of emergence from sedation. Ninety‐four paired determinations of Cmeas and Cpred from 15 adult ASA I patients (8 men and 7 women 54.9 ± 13 years old; BMI, 24 ± 3.2 kg/m 2 ) were analyzed. Mean duration of drug administration was 31 ± 6 hours. The coefficient of determination ( R 2 ) of the linear regression model for the relationship of Cmeas and Cpred was 0.43. At the time of emergence, Cmeas was 0.5 ± 0.18 μg/mL. The bias of the TCI system (median performance error) was ‐34.7%, and the precision (median absolute performance error) was 36%. Wobble and divergence were 0.3% and 12.3%, respectively. This study found bias of the system out of the range of tolerability and showed a high tendency toward overestimation. These findings may lead to undersedation when propofol TCI is used for prolonged infusion.